Evaluation of benefit to patients of training mental health professionals in suicide guidelines: Cluster randomised trial. (May 2016) - de Beurs, Derek P.; de Groot, Marieke H.; de Keijser, Jos; van Duijn, Erik; de Winter, Remco F. P.; Kerkhof, Ad J. F. M.
Abstract : Background: Randomised studies examining the effect on patients of training professionals in adherence to suicide guidelines are scarce. Aims: To assess whether patients benefited from the training of professionals in adherence to suicide guidelines. Method: In total 45 psychiatric departments were randomised (Dutch trial register: NTR3092). In the intervention condition, all staff in the departments were trained with an e-learning supported train-the-trainer programme. After the intervention, patients were assessed at admission and at 3-month follow-up. Primary outcome was change in suicide ideation, assessed with the Beck Scale for Suicide Ideation. Results: For the total group of 566 patients with a positive score on the Beck Scale for Suicide Ideation at baseline, intention-to-treat analysis showed no effects of the intervention on patient outcomes at 3-month follow-up. Patients who were suicidal with a DSM-IV diagnosis of depression ( n = 154) showed a significant decrease in suicide ideation when treated in the intervention group. Patients in the intervention group more often reported that suicidality was discussed during treatment. Conclusions: Overall, no effect of our intervention on patients was found. However, we did find a beneficial effect of the training of professionals on patients with depression.